Chemical analysis of extracellular vesicles by synchrotron-based X-ray imaging and scattering techniques: a review and perspective - Huang, Li; Chen, Yan; Guo, Xiutian; Zhou, Limin (Frontiers in Bioengineering and Biotechnology, 2026)
Extracellular vesicles (EVs) are nanoscale lipid bilayer-enclosed particles released by cells, which have been explored as pivotal mediators for intercellular communication, biomarkers for diseases and nano-carriers for drug delivery. Unraveling their structural and chemical heterogeneity is crucial for understanding the biogenesis, cargo sorting, and functional mechanisms of EVs. However, by far it remains challenging to characterize the intrinsic physicochemical properties of EVs due to their varied intracellular origins, poly-disperse size distribution and dynamic membrane organization. Conventional imaging and light scattering methods either lack the chemical sensitivity or suffer from labeling artifacts. Here in this review, we summarize research work using synchrotron-based X-ray imaging and scattering techniques to resolve the chemical structural complexity of EVs with intrinsic chemical specificity and enhanced sensitivity. The feasibility and effectiveness of X-ray imaging and scattering tools on quantifying critical structural parameters of EVs including morphology, core-shell and bilayer structure is discussed. We hope it will inspire future in-depth work to bridge the gap between structural and biological functionality in EVs research.